Analysis of Scattering Influence and Shielding Effect of Rear Collimator in Large Object Radiation Imaging System - DONG Tao;LIU Ximing;XING Guilai;WANG Zhentao;HUANG Yibin;LIU Jinhui;WU Zhifang (Yuanzineng kexue jishu, 2023)
In large object radiation imaging system, the interaction between medium and high energy (MeV) X/γ-ray and matter is dominated by Compton scattering, which produces a large number of the scattered particles. And the influence of the scattered particles on the radiographic images has always been a tough problem that plagues the developers. And the rear collimator is commonly used to reduce the influence of the scattered particles and improve the quality of the radiographic images. At present, the relevant research mainly analyzes the distribution of the scattered particles in the detector array, but there is a lack of research on the distribution of the scattered particles on the surface of the inspected object. Based on the Monte-Carlo simulation model of the 60Co large object radiation imaging system, a common medium-density substance (iron plate) was selected as the inspected object, and the number distribution and energy distribution of the scattered particles were analyzed in detail when γ-ray penetrates iron plates from different positions and with different thicknesses. Also, the diffusion effect of the scattered particles and the shielding effect of the rear collimator on the scattered particles were analyzed. There are some results drawn in this paper. In the horizontal direction, the diffusion effect of the scattered particles caused by multiple Compton scattering is limited, and most of the scattered particles come from the area covered by the initial γ-ray beam on the object. About 90% of the scattered particles have a horizontal distribution range of 40-70 mm on the surface of the object, which will limit the shielding effect of the rear collimator. When the distance S between the iron plate (with the thickness of 100 mm) and the detector array is reduced to the limit of 500 mm for safe driving, there is approximately 39.74% of the scattered particles shielded by the rear collimator (Fe) with the collimation ratio of 20∶1 and the best thickness of 5 mm, while the ideal rear collimator absorbing all incident particles can shield about 63.21% of the scattered particles. When the distance S increases to 1 750 mm or more, the scattering effect of the rear collimator will be severe and cause an increase in the number of the scattered particles instead of performing its function of shielding the scattered particles, and a wider rear collimator may cause more serious scattering interference. Therefore, in the large object radiation imaging system, the scattering effect of the rear collimator cannot be ignored, and its shielding effect on the scattered particles is also limited.